An RNAi screen identifies KIF15 as a novel regulator of the endocytic trafficking of integrin - Es'kova, Anastasia; Knapp, Bettina; Matelska, Dorota; Reusing, Susanne; Arjonen, Antti; Lisauskas, Tautvydas; Pepperkok, Rainer; Russell, Robert B.; Eils, Roland; Ivaska, Johanna; Kaderali, Lars; Erfle, Holger; et al. (Journal of cell science, 2014)
Skip to Next Section - α2β1 integrin is one of the most important collagen-binding receptors, and it has been implicated in numerous thrombotic and immune diseases. α2β1 integrin is a potent tumour suppressor, and its downregulation is associated with increased metastasis and poor prognosis in breast cancer. Currently, very little is known about the mechanism that regulates the cell-surface expression and trafficking of α2β1 integrin. Here, using a quantitative fluorescence-microscopy-based RNAi assay, we investigated the impact of 386 cytoskeleton-associated or -regulatory genes on α2 integrin endocytosis and found that 122 of these affected the intracellular accumulation of α2 integrin. Of these, 83 were found to be putative regulators of α2 integrin trafficking and/or expression, with no observed effect on the internalization of epidermal growth factor (EGF) or transferrin. Further interrogation and validation of the siRNA screen revealed a role for KIF15, a microtubule-based molecular motor, as a significant inhibitor of the endocytic trafficking of α2 integrin. Our data suggest a novel role for KIF15 in mediating plasma membrane localization of the alternative clathrin adaptor Dab2, thus impinging on pathways that regulate α2 integrin internalization.